Changes in the network structure of energy markets and financial markets under the different shocks of the Russia-Ukraine conflict and COVID-19 - Fuyao Li; Mu Tong; Shuhao Guan (PLoS ONE, 2025)
Employing the quantile coherency method, we analyze the different impacts of the Russia-Ukraine conflict and the global shock caused by COVID-19 on energy and stock markets, highlighting how market behaviors varied under these two crises. The findings reveal that natural gas performed better than oil during the pandemic and the Russia-Ukraine conflict in the short and medium term. In contrast, oil outperforms natural gas over the long term.